Enhancing hydrogen evolution by photoelectrocatalysis of water splitting over a CdS flowers-loaded TiO2 nanotube array film on the Ti foil substrate. Issue 11 (1st August 2020) - Zhang, Yuyuan; Hu, Huawen; Kang, Wanwen; Qiu, Guojian; Liang, Ruiyin; Deng, Lifang; Yuan, Haoran
Abstract: This study is devoted to the scalable fabrication of a high-performance composite photocatalyst by incorporation of the visible-light-active CdS flowers (with sharp edges exposed) onto a TiO2 nanotube array (TNA) film on the Ti foil substrate. To evaluate the visible-light-harvesting performance of the prepared hierarchical architecture consisting of the CdS flowers, TNAs, and Ti foil, we subsequently assembled a photoelectrochemical (PEC) cell with membrane electrode assemblies fabricated innovatively by thermocompression. The CdS flowers can efficiently harvest the visible light energy, while TiO2 collects photoelectrons, effectively separating of the photoexcited electron-hole pairs and hence enhancing the photocatalysis efficiency in the photoelectrochemical conversion and yield of hydrogen production from water splitting. An impressive hydrogen production rate of 22.44 μmol▪h −1 ▪cm −2 was obtained in the PEC cell with the CdS flowers-sensitized TNA film under simulated solar light with an active irradiation area of around 42 cm 2, thus showing great potential for practical applications.